Carotid intima-media thickness and flow-mediated dilation in obese children with non-alcoholic fatty liver disease - Torun, Emel; Aydın, Sinem; Gökçe, Selim; Özgen, İlker Tolga and Donmez, Tuğrul and Cesur, Yaşar (Turkish Journal of Gastroenterology, 2014)
Abstract Background/Aims: This study aimed to understand the role of non-alcoholic fatty liver disease (NAFLD) in increasing the risk of atherosclerosis in obese pediatric patients. Materials and Methods: The study included 109 obese children (age, 9-15 years) and a control group comprising 44 healthy age- and gender-matched children with normal weight. NAFLD was diagnosed using conventional ultrasound (US) examination. Both right carotid intima-media thickness (CIMT) and flow-mediated dilation (FMD) were assessed in addition to anthropometric measures and serum biochemical parameters, including lipid profile and fasting glucose and insulin levels. Homeostatic model assessment of insulin resistance (HOMA-IR) was calculated as a measure of insulin resistance. Results: Mean age and gender distributions were similar in the obese children and control group (p=0.168 and p=0.705, respectively). Median body mass index standard deviation scores of obese children with grade II-III NAFLD were significantly higher than those of obese children without hepatosteatosis (p<0.001). Median total cholesterol levels were similar in all the groups (p=0.263). Low-density lipoprotein cholesterol and triglyceride levels increased and high-density lipoprotein cholesterol levels decreased significantly as the grade of steatosis increased (p<0.001, p<0.05, and p=0.05, respectively). Median alanine aminotransaminase (ALT) and HOMA-IR levels of obese children with grade II-III NAFLD were significantly higher than those of obese children without NAFLD (p=0.01) and obese children with grade I NAFLD (p=0.001). CIMT was significantly correlated with the grade of steatosis (p<0.001) and level of ALT (p=0.005). Linear regression analysis showed that the grade of hepatosteatosis had a significant effect on CIMT. FMD decreased as the grade of hepatosteatosis increased, but it did not reach a significant level. Conclusion: The obese children with hepatosteatosis showed increased CIMT, as indicated by the grade of steatosis, compared with healthy controls and obese children without hepatosteatosis. FMD was not superior to CIMT in predicting the risk of early atherosclerosis.